Yuridis Putusan Mahkamah Konstitusi Nomor 35/PUU-X/2012 Tentang Keberadaan Hutan Adat Masyarakat - Syaiful Rachman; Mansyur Nawawi; M Chairul Basrun Umanailo (Mahesa Research Center, 2021)
In principle, forest and forestry management is a management process for all components of the ecosystem, including humans. Utilization of forests to facilitate economic growth has eliminated the interests of customary forest communities, the rights of indigenous peoples have been protected as human rights, as stated in Law Number 39 of 1999 concerning the basic provisions of human rights. The people of Buru District, Grandeng Village, have an area of forest area for other uses of around 600 hectares which can be used for the benefit of local communities, but there are often problems between the Transmigration Community and Indigenous People who have unresolved ownership of land areas based on customary law, as well as the involvement of the local government Buru Regency in providing solutions to problem-solving, the method used is descriptive qualitative with interview instruments and a review of legal documents related to the research theme. The results that can be conveyed are the utilization of Customary forest products and their management by the community in Lolongguba sub-district, often in coordination with Hinolong Baman or the Head of Soa, which means that legally the implementation of the Constitutional Court Decision, No.35 / PUU-X / 2012 concerning the Existence of Community Customary Forests has been implemented in the community, however, the institutionality of the Waeapo Plains Indigenous Peoples has not been maximized, both in the implementation of customary law norms, as a result of factors, human resources, economy, social and Indigenous institutions themselves. Based on legal research, it is necessary to formulate a legal umbrella both government regulations and regional regulations regarding ownership of forests and forest products.